The Effect of Using Recycled Aggregates on Concrete Durability Indicators (Capillary Absorption and Total Water Immersion) - علي خيربك,; بسام حسن,; باسل أصلان , (Latakia University Journal -Engineering Sciences Series, 2023)
Recycled aggregate is considered a substitute for natural gravel, which resulted due to harsh climatic conditions or natural or human disasters, and was formed in our country in particular because of the war we are living through, and the resulting operations of demolishing and vandalizing facilities and the accumulation of large quantities of demolition debris, those factors that together will secure large quantities of recycled gravel, which enables it to be widely used as a substitute for natural gravel. The results of the tests conducted on the concrete samples in which the natural aggregates were replaced with recycled aggregates with different replacement rates (0%-20%-30%-50%-100%) were positive. As for the durability studies, they are relatively few because they require a long time and techniques. Advanced to investigate the structure of concrete after exposure to destructive conditions in order to determine its useful life. From here it was necessary to study the change of the characteristics of this concrete with time and to study its durability under the influence of many factors (capillary absorption and total immersion in water) and to measure the extent of the effect of replacing natural stones with recycled stones on the durability properties. The results of the research show good values for the durability indicators of concrete manufactured using recycled aggregates compared to concrete manufactured from natural aggregates only. Durability indicators improve up to 50% replacement rate with regard to capillary absorption and total immersion in water.